KEMAMPUAN BACA TULIS AL-QUR’AN DAN PEMBELAJARAN BAHASA ARAB: KAJIAN STUDI LITERATUR TERHADAP KETERKAITAN, HAMBATAN, DAN METODE PEMBELAJARAN - amelia, flora; Sahrul Gunawan, Asep (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is a literature review aimed at analyzing the relationship between Quranic literacy (BTQ) and Arabic language learning. By examining fifteen relevant scientific articles published between 2017 and 2025, this research investigates the dimensions of their interconnection, identifies key learning obstacles, and maps effective teaching methods. The findings reveal a significant and mutually reinforcing relationship between BTQ competence and Arabic language achievement. Empirical data show correlation coefficients ranging from r=0.681 to r=0.983, indicating strong to very strong relationships. Quranic reading ability contributes 66.8% to Arabic learning outcomes (Hijriyah et al., 2020), Arabic proficiency explains 46.35% of Quranic memorization variance (Zubaidillah, 2018), and the correlation between Quranic reading skill and Arabic text reading skill reaches r=0.693 (Triyana et al., 2024). This study identifies six relational patterns between BTQ and Arabic learning, including their reciprocal nature, the role of BTQ as a linguistic foundation for maharah al-kitabah, and the significance of learning context. An integrative approach combining Quranic learning with communicative and applied-linguistics-based Arabic instruction is recommended.